The Issue of Suffering in Program Documents and Selected Methodological Guides for Teaching Religion - Bielinowicz, Adam Przemysław (Studia Warmińskie, 2022)
Suffering, in different dimensions and at different times, affects each of us, putting the human sense of its meaning to the test. Without God, it is impossible to understand the meaning of the value of this experience. One of the tasks of the Church is to reach the sick with ministry by preparing the faithful to properly understand and experience suffering following Christ's example. This task should be undertaken, inter alia, during religious education and catechesis. The article indicates the provisions on the issue of suffering present in the documents programming religious education and in selected methodological guides, as well as formulates conclusions and postulates regarding the content that should be conveyed by catechists. The aim of the article is to try to answer the question to what extent can a religion lesson help the catechized to understand the problem of suffering?